Technology transfer for renewable energy : overcoming barriers in developing countries - Wilkins, Gill (Earthscan : Royal Institute of International Affairs, 2002)
"This text highlights the role that renewable energy can play in achieving sustainable development. It focuses on rural areas of developing countries, looking in particular at stand-alone solar home systems and grid-connected biomass cogeneration plants. It analyzes the main barriers to the successful transfer of renewable energy technology, with case studies from a range of South-East Asian, South Asian, Pacific and African countries, and explains the ways in which these obstacles can be overcome. The roles of the key players involved and how the Kyoto Protocol can facilitate the transfer in order to mitigate climate change are also discussed"--Provided by publisher